Electrochemical treatment of Produced Water using Ti/Pt and BDD anode - Campos, Viviane de Oliveira; Amaral, Leticia Bezerra do; Sales Solano, Aline Maria; Araujo, Danyelle Medeiros de; Martinez-Huitle, Carlos A. [UNESP]; Silva, Djalma Ribeiro da (Esg, 2018)
The applicability of electrochemical oxidation (EO) to treat a real petrochemical effluent was investigated using a lab electrochemical cell and pre-pilot plant scale reactor with Ti/Pt and BDD anode materials. The efficacy of EO in treating a real effluent was determined and the reactors compared at different applied current densities (j = 15, 30 and 60 mA cm(-2)). The results clearly indicate that an electrochemical pre-pilot reactor removes more than 97% of dissolved organic matter applying 15 mA cm(-2) at pH 6.0 and 25 degrees C after 30 min of electrolysis, consuming 3.37 kWh m(-3), and incurring a cost of around 0.57 USD m(-3). The results obtained provide valuable information regarding the EO scaling-up process, aimed at applying electrochemical technologies to treat actual effluents on a real scale.
Keywords: produced water; platinum; wastewater treatment; anodic oxidation; diamond electrode